FRI0634 Do anthropometric factors influence median nerve size in healthy individuals? an ultrasound and volumetry study. (15th June 2017) - O'Neill, A; Gardiner, P; McCormick, D; Savage, E; Small, D
Abstract : Background: Some (but not all) ultrasound studies of median nerve dimensions at the wrist have suggested that anthropometric factors such as height and weight are among the possible sources of variability in the normal population but this has not been systematically studied 1 . Objectives: The purpose of our study was to establish if hand and wrist volume or other standard anthropomorphic factors influenced median nerve size in normal subjects using standard ultrasonographic techniques. If median nerve size is predictably related to anthropomorphic factors, adjusted normal reference ranges would improve the diagnostic precision of the test for carpal tunnel syndrome. Methods: We studied 30 healthy subjects: 14 females and 16 males. We measured their height, weight, arm span, finger span and wrist circumference. Ultrasonography of the median nerve was carried out at the entrance to the carpal tunnel and at a second level 2 cm proximal to the wrist using an Esaote MyLab Class C ultrasound with a 12–18MHz linear probe. The wrist was marked at the distal wrist crease and 2cm proximally. Hand and wrist volume were measured using water displacement volumetry. Results: The intra-rater reliability of volumetry measurements was excellent for both hand and wrist volumetry with a Cronbach alpha of 0.99 and 0.88 respectively. The intra-rater reliability for median nerve measurements was excellent with a Cronbach alpha of 0.96. The median nerve dimensions were not significantly different between male and female subjects, nor between the dominant and non-dominant hands. The mean median nerve cross sectional area (CSA) at the distal wrist crease was 10.68 mm 2 and at a point 2cm proximal to this it was 10.18 mm 2 . The mean difference in CSA between these two points was 0.5 mm 2 . The median nerve CSA was not significantly related to height, weight or hand size. It was not correlated with hand or wrist volume. No significant differences were found in relation to hand dominance or gender. Conclusions: Anthropometric factors including BMI, hand/wrist volume were not found to be closely related to median nerve size in normal individuals. References: Cartwright MS et al. Ultrasonographic reference values for assessing the normal median nerve in adults. J Neuroimaging. 2009;19(1):47–51. Disclosure of Interest: None declared